(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
Architecture exerts a profound impact on the cultural construction of light and shadow, influencing how individuals perceive and interact with space. Light is not merely a physical phenomenon, but also a symbolic element that can shape consciousness. In this context, it is important to distinguish light as an entity in itself from the ways in which it is conceived, distributed, and applied in built environments. When guided by logics of control, productivity, or excess, particularly in the context of artificial lighting, light can condition, affect, and interfere with physical and mental well-being. The relationship between architecture, light, and the brain is thus revealed to be profound and multifaceted. It is hoped that this essay, based on a literature review, will constitute a relevant contribution to critical reflection on the conception of light.